2015
DOI: 10.5455/msm.2015.27.248-250
|View full text |Cite
|
Sign up to set email alerts
|

Doctors' Preferences for Controlled Ovarian Stimulation Protocols in Intrauterine Insemination

Abstract: Introduction:Intrauterine insemination (IUI) is an important treatment for infertility. IUI combined with controlled ovarian stimulation (COS) is widely used because of the higher pregnancy rates compared to IUI cycles without COS.Material and methods:We retrospectively analyzed a single center data from 458 patients underwent the first IUI cycle and had only 1 mature follicle from May 2009 to January 20144. 48 cycles were performed with Clomiphene citrate/Letrozole (CC/LE), 244 cycles with gonadotropins (Gn),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
1
Order By: Relevance
“…Instead, there was no significant difference about pregnancy rates between single and multiple follicular growth cycle, no matter the growth follicle with an average diameter of at least 15 mm or 10 mm [19]. Zeng et al concluded that the success rate of one dominant follicle induced and natural IUI cycle was similar [22]. In our study, clinical pregnancy rate rose in either one or two follicle induction cycles.…”
Section: Discussioncontrasting
confidence: 50%
“…Instead, there was no significant difference about pregnancy rates between single and multiple follicular growth cycle, no matter the growth follicle with an average diameter of at least 15 mm or 10 mm [19]. Zeng et al concluded that the success rate of one dominant follicle induced and natural IUI cycle was similar [22]. In our study, clinical pregnancy rate rose in either one or two follicle induction cycles.…”
Section: Discussioncontrasting
confidence: 50%